1988
DOI: 10.1190/1.1442433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of source spectrum on seismic attenuation measurements using the pulse‐broadening method

Abstract: Numerical examples of one‐dimensional (1-D) wave propagation, using realistic source time functions in an anelastic material characterized by frequency‐independent internal friction, demonstrate that (a) the source time function strongly influences the dependencies of initial rise time τ and pulse width w on internal friction [Formula: see text] and distance x; (b) in general, τ and w have different functional dependencies on [Formula: see text] and x; and (c) the slope ∂τ/∂x for particle displacement computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…One may think that the source parameters inferred in this study are strictly dependent on the assumptions inherent to the adopted source model (i.e. Then, by considering the inelasticity of rocks, other than the source contribution to the pulse width, one must account for the attenuation term, given by Ct/Q, where C is dependent on the source time function, as shown in several papers (Liu 1988;de Lorenzo 1998). As we will try to show, the obtained results are slightly more general and inherent to the basic assumptions of kinematics of the seismic source.…”
Section: Discussion a N D C O N C L U S I O Nmentioning
confidence: 99%
“…One may think that the source parameters inferred in this study are strictly dependent on the assumptions inherent to the adopted source model (i.e. Then, by considering the inelasticity of rocks, other than the source contribution to the pulse width, one must account for the attenuation term, given by Ct/Q, where C is dependent on the source time function, as shown in several papers (Liu 1988;de Lorenzo 1998). As we will try to show, the obtained results are slightly more general and inherent to the basic assumptions of kinematics of the seismic source.…”
Section: Discussion a N D C O N C L U S I O Nmentioning
confidence: 99%
“…The value of C was experimentally determined for ultrasonic acoustic pulses to be 0.5 [ Gladwin and Stacey , 1974], whereas a theoretical demonstration, based on an impulsive displacement source, was given by Kjartansson [1979]. Further studies [ Blair and Spathis , 1982; Liu , 1988; Wu and Lees , 1996] have shown that C depends on the shape of the source time function. A C value of 0.5, corresponding to an impulsive displacement function, is commonly used.…”
Section: Theory and Nonlinear Inverse Methodsmentioning
confidence: 99%
“…This is performed by assuming the circular crack model proposed by Sato and Hirasawa [1973]. With respect to other time domain modeling techniques [Liu, 1988;Wu and Lees, 1996;de Lorenzo, 1998] the equations we derived, constitute other theoretical evidence for nonlinearity among rise times and travel times, and are also able to account for the directivity of the seismic source. In this paper the explicit dependence of the slope of 'c versus t* on the frequency content at source through the function •P0, c, 0) has been obtained by considering the SH circular crack model.…”
Section: Discussionmentioning
confidence: 99%
“…The controversy about the applicability of the rise time method to signals generated by sources characterized by a finite frequency content is well documented in literature [Blair and Spathis, 1982;Liu, 1988;Zucca et al, 1994;Wu and Lees, 1996]. Zucca et al [ 1994] applied the rise time method to study the attenuation properties of the Geysers geothermal field.…”
Section: Pulse Width (Or Rise Time) Methodsmentioning
confidence: 99%